Export Performance and Survival in Russia: Why some Regions grow fast and others don't - Sergey Kadochnikov; Anna Fedyunina (FIW - Research Centre International Economics, 2015)
In this paper, we investigate the relationship between export performance and economic growth in Russian regions. We propose a methodology for decomposition of export growth into intensive and extensive margins and distinguish between product- and geographic extensive components within extensive margin. An empirical analysis suggests that higher growth rates in Russian regions are associated with higher intensive margin. We reveal significant differences in export survival of differentiated and homogeneous flows and find evidence of strong effects of distance and institutions on export survival. We argue that Russian regions would experience higher economic growth if they were able to improve their export performance at the intensive margin by providing lower transport costs to the business and by enhancing higher quality of institutions.
Keywords: F14; R1; 330; export performance; economic growth; intensive margin; extensive margin; export survival; Russian regions